A new Peruvian land planarian species of the genus Gigantea (Platyhelminthes, Tricladida, Geoplanidae) - Negrete, Lisandro Hector Luis (2010)
A new species of Geoplaninae land planarian from south Peru, Gigantea urubambensis sp. nov., is described. The most outstanding features of the new species are the very dorsal location of the testes, between the dorsal diagonal and the supra-intestinal parenchymatic muscle layers; a penis papilla projecting from the roof of the male atrium and acentrally traversed by the ejaculatory duct; and the absence of glandular ridges on the penis papilla.